LOW CD4 LYMPHOCYTE COUNT RELATED RISK TO Pneumocystis jiroveci PNEUMONIA IN HIV/AIDS PATIENTS FROM BRONCHOALVEOLAR LAVAGE SPECIMENS USING REAL TIME PCR DETECTION - Widya, Alicia Margaretta; Mertaniasih, Ni Made; Kawilarang, Arthur Pohan; Marhana, Isnin Anang (Indonesian Journal of Tropical and Infectious Disease, 2017)
HIV and opportunistic infections remain a big problem especially in developing country. Pneumocystis jiroveci pneumonia is a prevalent infection  in HIV infected patient with high mortality rate. Diagnosis of Pneumocystis jiroveci pneumonia is mainly based on clinical evidence. Microbiological diagnosis is quite challenging since this microorganism cannot be cultured and is mainly based on microscopic examination. Microscopic examination with special staining is still a gold standard diagnosis for P. jiroveci infection.The objectives of this study was to describe CD4 lymphocyte profile and establish microbiological diagnosis with recent molecular method in PJP suspected HIV positive patients. Fiberoptic bronchoscopy of HIV infected patients with lower respiratory tract infection in Dr. Soetomo general hospital Surabaya were performed to collect bronchoalveolar lavage specimens  from December 2016 to April 2017 for identification of Pneumocystis jiroveci using real time PCR assay. Positive samples were then evaluated for  microscopic examination with Gommori Methenamine Silver staining for comparison. Patient's CD4 lymphocyte count were gathered prior of admission. CD4 lymphocyte count from this study were very low with 61% of the patients were below 50 cells/ µL. There were five of  total thirteen patients (38,5%) with positive real time PCR assay (MSG gene)  and one patient was also positive with GMS staining showing characteristic cysts shape with dark centered area of P. jiroveci. Patient with positive microscopic examination showed no history of prophylactic therapy. Low CD4 lymphocyte count remains a strong risk factor of P. jiroveci pneumonia in HIV/AIDS patients. Real time PCR assay shows high value in detection of P. jiroveci regarding patient's prophylactic status.